2023
DOI: 10.2174/1573403x18666220322092706
|View full text |Cite
|
Sign up to set email alerts
|

Quadricuspid Pulmonary Valve: Case Report and the Comparison with Quadricuspid Aortic Valve

Abstract: Background: Quadricuspid pulmonary valve (QPV) is a rare congenital anomaly. Simple QPV had been mainly diagnosed at the time of autopsy before 2000 and the frequency rates of QPV are approximately 0.02%–0.41%. QPV was initially diagnosed using transthoracic echocardiography (TTE) after 2000 and with contrast computed tomography (CT) or cardiac magnetic resonance imaging (CMR) after 2009. Obtaining the cross-sectional view of the pulmonary valve using TTE is difficult. We aimed to review the papers regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…The supernumerary leaflets are generally asymptomatic and isolated; also, they can rarely cause dysfunction and are more commonly associated with other congenital cardiac abnormalities [ 11 ]. Interestingly, combining data from two studies, Hurwitz et al's [ 10 ] and Davia et al's [ 6 ], of the 193 QPVs found at necropsy, only eight (4%) were not fully functional [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernumerary leaflets are generally asymptomatic and isolated; also, they can rarely cause dysfunction and are more commonly associated with other congenital cardiac abnormalities [ 11 ]. Interestingly, combining data from two studies, Hurwitz et al's [ 10 ] and Davia et al's [ 6 ], of the 193 QPVs found at necropsy, only eight (4%) were not fully functional [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, QPVs can be associated with congenital cardiac abnormalities such as patent ductus arteriosus, atrial or ventricular septal defects, and bicuspid aortic valves [ 12 ]. In fact, compared with QAVs, QPVs are more often coexistent with congenital heart anomalies and valvular stenosis (but less frequently coexistent with coronary artery anomalies and infectious endocarditis) [ 11 ]. Because of its association with other cardiac abnormalities, understanding the embryology of valvulogenesis and how these abnormalities might arise is critical.…”
Section: Discussionmentioning
confidence: 99%